From Big Bang to the Big Band (2021)
The present literary essay approaches the controversy between the symbolic world in which the old inhabitants of the planet and the post-nuclear scientific world lived, where all myth has been supplanted to us by a rational vision of our origin. It doesn´t interest us here to clarify the “truth or falsification” of the ancestral traditions to which we contrast with the scientific hypotheses of the big bang, but to track the existential consequences that fall on the human beings, from the adoption of a certain image of how it was its origin, that is also the principle of the universe. Finally, an alternative and artistic, poetical and metaphorical version is proposed, that serves as a myth for a possible future humanity, daughter of a creativity beginning whose potential is inconceivable